2002
DOI: 10.1007/s00104-002-0457-x
|View full text |Cite
|
Sign up to set email alerts
|

D3- versus D2-Dissektion beim Magenkarzinom Eine Fall-Kontroll-Studie hinsichtlich postoperativer Morbidität, Letalität und onkologischen Frühergebnissen

Abstract: Compared to the D2 method, D3 dissection is feasible without disadvantages in the patients. However, D3 dissection cannot routinely be recommended because--possibly due to the short follow-up period and the small number of patients so far observed--an oncologic benefit could not be shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Lymph nodes of compartment D1, including stage 7 (left gastric artery) in compartment D2, were removed en bloc with the resected gastric specimen. All other lymph nodes were defined by the surgeon and dissected individually during surgery [ 7 , 8 ]. We did not perform any prophylactic pancreatectomy or splenectomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymph nodes of compartment D1, including stage 7 (left gastric artery) in compartment D2, were removed en bloc with the resected gastric specimen. All other lymph nodes were defined by the surgeon and dissected individually during surgery [ 7 , 8 ]. We did not perform any prophylactic pancreatectomy or splenectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have found advantages in Roux-en-Y reconstruction, but this was not confirmed in other studies. The method learned by the surgeon and the associated operative experience undoubtedly play a major role [ 8 , 10 , 13 , 22 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chinese studies mortality and morbidity of D2 dissection was reported to be higher than D1 dissection, Finnish studies showed that D2 -3 dissection had higher complication rates as compared to D1 dissection and in Europe D2 -3 dissection is reported to carry an acceptable rate of mortality (17,18). German series also reported that D3 dissection is not superior to D2 dissection and D3 dissection has disadvantages (19,20). In our study, the greater omentum, D1 lymph node dissection, and 7, 8, 9 lymph nodes were removed as part of total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%